2010
DOI: 10.1007/s10856-010-4066-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical alloying of biocompatible Co–28Cr–6Mo alloy

Abstract: We report on an alternative route for the synthesis of crystalline Co-28Cr-6Mo alloy, which could be used for surgical implants. Co, Cr and Mo elemental powders, mixed in an adequate weight relation according to ISO Standard 58342-4 (ISO, 1996), were used for the mechanical alloying (MA) of nano-structured Co-alloy. The process was carried out at room temperature in a shaker mixer mill using hardened steel balls and vials as milling media, with a 1:8 ball:powder weight ratio. Crystalline structure characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…In the second mixture, the effect of Mo on the amorphization of Co was studied; in this case, 10% in weight of Mo was MA with elemental Co (according with previous work [12]). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second mixture, the effect of Mo on the amorphization of Co was studied; in this case, 10% in weight of Mo was MA with elemental Co (according with previous work [12]). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors [11] associated the amorphization with modification of the mill parameters, such as the ball-to-powder ratio, the charge volume or the milling time. Previous studies [12] demonstrated that MA is an effective method to obtain non-equilibrium phases in cobalt base alloys and helps to force the solubility and amorphization of different alloys [9,10,13].…”
Section: Introductionmentioning
confidence: 99%
“…The Severe Plastic Deformation (SPD), especially mechanical milling of powders, is an effective method to prepare fine-grained materials having extremely high strength. 4,5) However, homogeneous ultrafine grained materials suffer from the problem of extremely low ductility. 6,7) Therefore, it is required to prepare material having high strength and excellent ductility at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Alloys of this type generally demonstrate high levels of biocompatibility and also possess excellent mechanical properties, including resistance to pitting, wear, high abrasion and crevice corrosion, as well as showing high fatigue strength, malleability and ductility 3,4) . Co-Cr alloys are frequently used in implant materials during joint replacement procedures involving hard tissues, such as tooth and bone, where they come into direct contact with blood, soft tissue and bone 5,6) .…”
Section: Introductionmentioning
confidence: 99%